Upaya MEDIASI Pada Alternatif Penyelesaian Sengketa Dalam Perkara Sengketa Waris Litigasi Di Pengadilan Agama - Khoirun Nisa; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Mediation is a process in which several disputing parties try to find a solution together with the help of a neutral mediator. The mediator has a very important role in the success of mediation. Therefore, they must have good skills so that the mediation process can run smoothly and in accordance with the procedures regulated in PERMA Number 1 of 2008 concerning mediation procedures in Court. At every trial of a civil case in court, peace efforts must be made and mediation itself is an extension of peace efforts. Mediation will bridge the parties in resolving dead-end problems in order to reach or obtain the best solution for them. It is further emphasized that Religious Courts as family courts must not be intended as ordinary courts. This means, only exercising traditional judicial power and in resolving family disputes submitted to him.